Glutathione Content and Glutathione Peroxidase Activity of Sperm in Males with Unexplained Infertility - Danail Martinov; Nina Ayvazova; Emiliana Konova; Milena Atanasova (Journal of Biomedical & Clinical Research)
The study aimed to investigate glutathione peroxidase (GPx) activity and glutathione (GSH) levels in the sperm of patients with unexplained infertility. The sperm samples were collected from subjects with normal semen parameters divided into fertile and infertile groups. Sperm analysis was performed according to the 2010 WHO criteria. Measurement of the GPx activity and GSH were performed by enzymatic assay kits. The higher enzymatic activity recorded in spermatozoa and seminal plasma in the infertile group was close to the significant one – p=0.054 for seminal plasma andp= 0.086 for the spermatozoa.GSH levels were higher in the fertile group in the seminal plasma (p=0.045). Defining the causes of unexplained infertility requires the addition of oxidative stress. In patients with unexplained infertility, the level of glutathione is reduced, and the activity of one of the significant enzyme antioxidants GPx is not changed significantly and even shows a tendency to rise.